2016
DOI: 10.1002/path.4649
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo correlates of physiological and neoplastic human Fallopian tube stem cells

Abstract: High-grade serous cancer (HGSC) progresses to advanced stages without symptoms and the 5-year survival rate is a dismal 30%. Recent studies of ovaries and Fallopian tubes in patients with BRCA1 or BRCA2 mutations have documented a pre-metastatic intramucosal neoplasm that is found almost exclusively in the Fallopian tube, termed ‘serous tubal intraepithelial carcinoma’ or STIC. Moreover, other proliferations, termed p53 signatures, secretory cell outgrowths (SCOUTs), and lower-grade serous tubal intraepithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 53 publications
2
84
0
Order By: Relevance
“…Studies published so far have shown divergent roles of PAX2 depending on the tumor histotype(2325, 36, 37). Consistent with pathological observations, published microarray data indicates that PAX2 was significantly downregulated in STIC and HGSC tissues compared to normal FTE(27). A small subset of TCGA patients with amplification in the PAX2 gene, had a longer disease-free interval before relapse.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Studies published so far have shown divergent roles of PAX2 depending on the tumor histotype(2325, 36, 37). Consistent with pathological observations, published microarray data indicates that PAX2 was significantly downregulated in STIC and HGSC tissues compared to normal FTE(27). A small subset of TCGA patients with amplification in the PAX2 gene, had a longer disease-free interval before relapse.…”
Section: Discussionsupporting
confidence: 76%
“…In order to validate the clinical significance of PAX2 mRNA loss, microarray data from a Gene Expression Omnibus-GSE69429 was retrospectively analyzed by comparing PAX2 expression between normal FTE, STICs and invasive HGSC samples (n=6 per group)(26, 27). PAX2 expression progressively declined from STICs to HGSC when compared to normal FTE (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The third lesion is p53 signature, which is defined as a linear expansion of >12 of morphologically normal epithelium with p53 overexpression (12). This lesion shares identical p53 mutations and other genomic changes with HGSC, but lacks excessive cell proliferation (16). p53 signature is seen predominantly in continuity with STIC, localizes to the same (fimbria) region as STIC and shares preneoplastic properties with HGSC including p53 mutations (5,17).…”
Section: Histopathology Of Precursor Lesionsmentioning
confidence: 99%
“…Investigators have characterized the stepwise changes of molecular profiles identified by genomic, proteomic and immunohistochemical approaches, including BCL2 (BCL2 apoptosis regulator), p73 (tumor protein p73), PAX2 (paired box 2), p53, PAX8 (paired box 8), H2AX (H2A histone family member X), STMN1 (stathmin 1), EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit), Ki67, ALDH1A1 (aldehyde dehydrogenase 1 family member A1), CTNNB1 (β-catenin), CCNE1 (cyclin E1), LAMC1 (Laminin γ1), and HMGA2 (high mobility group AT-hook 2) genes and telomere shortening (Table I) (3,5,12,13,16,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Molecular Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation